Emergency of intraverbais from tact training with Precision Teaching - Moraes, Priscilla Terumi; Coimbra, Cláudia Stefânia Figueiredo Neves (Perspectivas em Análise do Comportamento, 2020)
Individuals with ASD (Autism Spectrum Disorder) may experience communication difficulties, such as deficits in the emission of intraverbal during social interaction. Over the years, researchers have been testing various procedures for teaching this skill (Kodak, Fuchtman and Paden (2012); McMorrow, Foxx, Faw, and Bittle (1987); Cihon, White, Zimmerman, Gesick, Stordahl & Eshleman (2017 )). This work aimed to evaluate whether the teaching of tacts thematically related to fluent levels could result in the emergence of intraverbals. A multiple baseline design was used between categories, of a single subject, and five teaching stages were performed: (1) tact training, (2) tact fluency training, (3) persistence probe (endurance), (4) stability probe and (5) retention probe. The results indicated that the intraverbal skill emerged from the fluent training of tacts thematically related to the use of Precision Teaching, without the need for direct training. Future studies can investigate the emergency with individuals who do not emit intraverbal for any category, and also compare the acquisition time between direct training and tact fluency training with the same subject. The present study has limitations regarding the context in which it was performed and participant (therapeutic setting and reinforcement history of following instructions), as well as the form of presentation of the stimuli (signaling of the temporal and visual categories).